Our nation desperate for more Professional Engineer - Wan Sharuzi, Wan Harun (2020)
The journey of an engineer begins from obtaining a scroll of an engineering degree till becoming a professional practitioner in their engineering field or better known as Professional Engineer (PE). Becoming a Professional Engineer is an end most achievement for all engineering graduate of any area. The recognition as one of Professional Engineers will provide a sense of triumph to anyone passionate to their engineering profession. The Professional Engineers will only deliver the tasks based on their most exceptional engineering knowledge, accurate problem analysis, optimum solution to the problem, comprehensive investigation and analysis, utilisation of best available tools, environmental and sustainability safeguard, a high priority of public safety, and sound judgement in project management through ethical practices. In Malaysia, there are various sectors of our engineers serving the nation from consultation, research & development, construction, building services, maintenance, manufacturing, plantation, aviation, maritime, sales, and oil & gas industry to the higher educational institutions like universities and colleges as a lecturer or a teaching engineer.